Optimum utilisation of IT in public administration - Gupta, R.G.; Gupta, Rita (2000)
Attempting to capture the scenario of computerisation in government offices, at Central, state and local levels, the authors give illustrations of success stories of some of the experiments being performed. They then give glimpses of IT success and suggest how best can this resource be utilised in rendering quality services. In the process, they highlight the hype created in the society by new technology and myths associated therewith. They discuss some measures to overcome the illusions spread in the society regarding computerisation and IT. The fact that active role of government is inevitable to make IT revolution a success in the country is duly justified by them. - Reproduced
Keywords: Public administration - India; Information technology - India; Information technology